1975
DOI: 10.1016/0010-4809(75)90037-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis. II. Diagnostic models based on attribute clusters: A proposal and comparisons

Abstract: A few patients had class "4" history grades but no positive radio-allergosorbent test results. This may indicate an allergen yet to be discovered-possibly an occupational one-a non-IgE-mediated mechanism or perhaps an exceptional interference in the radio-allergosorbent test by antibodies of another class. Whatever the reason, in such cases referral to an allergy specialist would be recommended. Indeed, referral should be considered when either the patient's symptoms are not fully explained by the report or ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Missing values were handled in the same way as in the independent Bayes model. Another way to account for interactions between variables in Bayes' theorem is the combination of Independence Bayes with cluster analysis [19]. It is the aim of this approach to form clusters of variables so that variables are conditionally dependent within a cluster and conditionally independent between clusters.…”
Section: B) Independence Bayes With Global Association Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Missing values were handled in the same way as in the independent Bayes model. Another way to account for interactions between variables in Bayes' theorem is the combination of Independence Bayes with cluster analysis [19]. It is the aim of this approach to form clusters of variables so that variables are conditionally dependent within a cluster and conditionally independent between clusters.…”
Section: B) Independence Bayes With Global Association Factormentioning
confidence: 99%
“…This model is the straightforward incorporation of pairwise interactions into the independent Bayes model. This approach is encouraging for many reasons: It is easy to understand by the clinician and simple to perform on a personal computer; it is theoretically more justified than Independence Bayes, and there have been good results in the few studies in the literature [16,18,19]. However, most of these promising models have not yet been compared with each other and with regard to standard popular models (Independence Bayes, linear logistic regression) using adequate methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these issues we proposed the GOM ll:10del-a model which differed in disease probability func-t~on from the posterior probability forms of logistic regres-SIon and cluster analysis. Specifically, we may relate GOM to logistic regression and Bayesian and linear discriminant analysis by defining a criterion event variable Yi and a set of predictor variables :lSi' In logistic regression the relation of Yi and :lSi may be expressed as log (8) where the regression weights in b T and the statistics ofthose weights are the desired quantities. In clinical settings :lSi is typically known and the true Yi is typically not (although a post .hoc groupin.p is often sub~ti.tuted for yJ In this case the predIctor Y i = b :lSi, (the logIstic score) performs the same function as the discriminant function score.…”
Section: Examplementioning
confidence: 99%
“…In a similar fashion, the Bayesian discriminant analysis is concerned with the analysis of a criterion variable Yi and a set of predictor variables :lSi. In this case, however, the :lSi are viewed as being drawn from a set of populations or classes where 10g(Plje/Paje) is analogous to b in (8) and log(l'tl/Jto) is analogous to the first term in (8). Thus, the same relation holds between GaM and Bayesian categorical discriminant analysis as between Fisherian discriminant analysis and logistic regression.…”
Section: Examplementioning
confidence: 99%
“…Experience suggests that the strong statistical assumption of conditional independence is invalid in many medical applications; some symptoms and signs do tend to eclipse others (e. g., [11]). Indeed, numerous studies have shown the presence of interactions in a variety of applications [12][13][14]. However, it does not necessarily follow that classifiers which take these interactions into account are more accurate.…”
Section: Introductionmentioning
confidence: 99%